(untitled) (Training and Practice : Journal of Educational Sciences, 2014)
The aim of the study is to survey the historical roots of the present Romany special circle, to introduce the one working at Kaposvár University, to examine its constitution and to give information about the results of the questionnaire filled in by the members of the special circle. This questionnaire was designed on the basis of the questions of a nation-wide survey, but it is not identical with that. The present questionnaire aims at mapping the composition and the attitude of the students’ membership. The most important indices are compared to the results gained from questionnaires at other special circles in Hungary. From the answers it can be concluded that the members are attracted to this college because of the atmosphere of the community as well as in the hope of getting some financial support.